Las periferias internas… ¿Absurdo... Contradicción o... realidad típica de la ciudad Latinoamericana? (2021)
This article proposes some ideas about the urban renovation in downtown areas, specifically refered to the latinamerican city’s case, taking into account a critic reflection of the predominant sthethic orientation that these processes have had in the past and the necessity of incorporate other visions about the problem of downtown recovery.